THE APPLICATION OF SCHOOL BASED MANAGEMENT IN IMPROVING STUDENT LEARNING OUTCOMES IN MADANI ISLAMIC JUNIOR HIGH SCHOOL ALAUDDIN PAO-PAO - Kasmawati Kasmawati (Universitas Islam Negeri Alauddin Makassar, 2019)
This article deals with the application of school-based management in Madani Islamic Junior High School (called madrasah tsanawiyah) at Pao-Pao. The main objective of this is to find out whether the application of school-based management can improve student learning outcomes in MTS Madani Alauddin Pao-Pao. The qualitative research is employed by the researcher, with a multidisciplinary approach. To obtain data, the authors do it with interview techniques, observation, and documentation to test the validity of the data using triangulation techniques. The results showed MTS Madani Alauddin Pao-pao, Gowa Regency, has implemented, but in practice it has not been maximized. This is because they still need ongoing assistance from competent parties. And still need assistance in the form of physical and non-physical from all relevant stakeholders so as to facilitate the implementation of MBS in Mts Madani Alauddin Pao-Pao (2) MTS Madani Alauddin Pao-pao, Gowa Regency, has an effort to improve student learning outcomes by: a ) provide a final assessment of the learning process that is carried out repeatedly, b) Provide an interesting learning method. In addition the teacher provides opportunities for students to work and participate in competitions or academic and non-academic olympiads, c) Provide motivation to students (3) In achieving the vision and mission of the school the application of school-based management can improve student learning outcomes in MTS Madani Alauddin Pao-Pao, Gowa Regency.